2013
DOI: 10.1063/1.4793760
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and temperature effects on intermolecular vibrational dynamics of ionic liquids

Abstract: Low frequency Raman spectra of ionic liquids have been obtained as a function of pressure up to ca. 4.0 GPa at room temperature and as a function of temperature along the supercooled liquid and glassy state at atmospheric pressure. Intermolecular vibrations are observed at ~20, ~70, and ~100 cm(-1) at room temperature in ionic liquids based on 1-alkyl-3-methylimidazolium cations. The component at ~100 cm(-1) is assigned to librational motion of the imidazolium ring because it is absent in non-aromatic ionic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 78 publications
1
33
0
3
Order By: Relevance
“…Penna and co-workers [16] observed Raman peaks around 3.8 and 10 meV at 300 K but could not identify the origin of the peaks. The glassy C4mimCl exhibits an excess vibrational excitation around 2 meV, demonstrating the presence of a boson peak.…”
Section: Incoherent Scatteringmentioning
confidence: 91%
See 1 more Smart Citation
“…Penna and co-workers [16] observed Raman peaks around 3.8 and 10 meV at 300 K but could not identify the origin of the peaks. The glassy C4mimCl exhibits an excess vibrational excitation around 2 meV, demonstrating the presence of a boson peak.…”
Section: Incoherent Scatteringmentioning
confidence: 91%
“…As for the ILs, the boson peak has been investigated mainly by Raman spectroscopy [14][15][16]. Ribeiro et al have investigated several types of ILs and found that the boson peak frequency is insensitive to the length of the alkyl-chain but depends on anions [16].…”
Section: Introductionmentioning
confidence: 99%
“…[71] Estas observações não se restringem a um ou outro extremo das escalas de tamanho ou de tempo, mas possuem implicações amplas, justificando transições de fase, como mencionado a transição vítrea, que é uma transição macroscópica e é verificada devido à observação de efeitos sobre tempos de relaxação estrutural da ordem de centenas de segundos, [70] e também a relaxação vibracional rápida (frequências da ordem de THz) associada no caso de substâncias amorfas ao pico de bóson, o qual é uma característica universal deste tipo de sistema. [72], [73] Uma função que é útil para o estudo deste tipo de processo em líquidos deve levar em consideração flutuações no tempo e no espaço. [29], [54]Uma função que atende estes critérios é o fator de estrutura dinâmico, S(Q,E) (ou alternativamente, S(Q,ω)).…”
Section: 9unclassified
“…[121] Alternativamente Normalmente, para o ajuste do espectro de baixa frequência, são atribuídas três bandas: uma banda, assumida lorentziana ou gaussiana, em torno de 100 cm -1 atribuída a libração do anel imidazólio (uma espécie de rotação impedida do anel), uma segunda banda em torno de 70 cm -1 (lorentziana ou gaussiana também) e, finalmente em torno de 15 cm -1 que tem sua forma funcional suposta uma função log-normal, atribuída ao pico de bóson. [73], [167], 115 [168] No caso de líquidos iônicos baseados em nitrato, o próprio ânion possui um modo de libração em torno 70 cm -1 associado à rotação impedida do ânion em torno do eixo C 2 , enquanto em líquidos iônicos baseados no ânions [NTf 2 ]uma banda extra deve ser incluída em 125 cm -1 . [21], [169], [170].…”
Section: Métodos De Função De Ondaunclassified
See 1 more Smart Citation